The effect of potassium iodide on the production of acid phosphatase by Sporothrix schenckii (Faculty of Medicine Universitas Indonesia, 2003)
The present study was undertaken to find out the in vitro effect of potassium iodide (KI) on the production of acid phosphatase by fully characterized strain of S.schenckii isolated from a patient of Cutaneous Sporotrichosis. The enzyme acid phosphatase was estimated during the 3 phases of growth of S.schenckii, without and with three concentrations of KI incorporated in the culture medium. In the control and in the test proper, with various concentrations of KI, no adverse effect of KI was observed on the production of acid phosphatase in early and mid log phase of fungal growth. Whereas in the exponential phase in test proper, there was a statistical significant decrease in the enzyme production with 0.8% and 3.2% of KI. The low activity at 0.8% and 3.2% KI indicates that KI has inhibitory effect on the growth of S.schenckii and has led to decrease in the activity of the enzyme. (Med J Indones 2003; 12: 65-8) Keywords: S.schenckii, acid phosphatase, potassium iodide